Stаtus Hukum Hаk Milik Аtаs Tаnаh yаng Terdаmpаk Likuefаksi - Triningtias, Ratnawati; Permаdi, Iwаn; Koeswаhyono, Imаm (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the legal status of property rights and the legal protection of holders of property rights on land affected by liquefaction. This study used a normative juridical method with a statutory approach and a conceptual approach. Ownership rights to land affected by liquefaction were still legally attached to the land owner because the land was not entirely lost but only shifted. Furthermore, land affected by liquefaction could not be categorized as destroyed land because it could physically be found based on coordinates. Legal protection for property rights holders on land affected by liquefaction was categorized into objective and subjective legal protection. Objective legal protection was carried out by re-measurement of the boundaries of property rights on land affected by liquefaction, digitally storing data on land ownership rights to overcome the impact of the loss of land title certificates due to disasters, as well as detailed spatial planning for disaster-prone areas. According to the detailed plan, personal legal protection was carried out by counseling and outreach to the public regarding disaster management and victim liquefaction relocation programs.